External debt and national economic growth: a case study of Nigeria (1990-2007) - Mikail, Shafiu Yahya (Kulliyyah of Islamic Revealed Knowledge and Human Sciences,International Islamic University Malaysia, 2012)
Foreign aid is considered as a significant source of income for developing countries. Countries that were facing current account deficit in the 1950s were encouraged to borrow from international financial institutions to boost their economic growth. However, such borrowing created a great obstruction in the economic growth of many developing countries today due to high interest payments on the external debt. Hence, it has been observed that in the past three decades external debt has been the main cause of decline in investment and economic growth of many developing countries. Like many developing countries, Nigeria has borrowed money from international financial institutions to finance its structural deficit. Currently, the country's foreign debt has been a persisting national problem affecting national economy. For this reason, the external debt problem has been receiving attention by academicians and policy makers. This study aims to examine Nigeria's external debt and its economic grow1h performance during 1990-2007. The central argument of the research is that external debt affects economic growth, and in the case of Nigeria, external debt has heavily affected its economic growth. The negative impact of external debt is measured by comparing the annual debt service with the ratio of government expenditure in the selected six out of eight Millennium Development Goals (MDGs), whereby it shows that Nigeria's government has not been able to allocate sufficient recourses towards the realization of the Millennium Development Goals (MDGs) due to its obligation to channel a substantial percentage of GDP to meet external debt service.